Translation and Cross-Language Validation of the Positive & Negative Affect Scale (PANAS) in Urdu Language - Dr. Anila Sadaf Mubashir; Rida Kainaat; Samia Azeem; Rizwana Amin; Saleha Ahmed (Research Journal of Psychology, 2025)
The present study aimed to translate the Positive and Negative Affect Scale (PANAS) into the Urdu language and to validate its psychometric properties within the Pakistani context. The study was conducted in three phases. Phase I included forward translation, reconciliation, and back translation of the PANAS, conducted by expert psychologists and linguists. Phase II involved assessing cross-language validity with a sample of bilingual adults. Phase III was dedicated to establishing the scale’s factor structure and reliability using a sample of 195 participants. Confirmatory Factor Analysis (CFA) and reliability analysis were conducted to evaluate the psychometric strength of the Urdu version. High correlations (.82 to .90) between the English and Urdu versions confirmed empirical equivalence. CFA results demonstrated acceptable model fit (GFI = .720, AGFI = .911, RMSEA = .065), though some indices (CFI = .800, TLI = .80) were marginal. Internal consistency (Cronbach's alpha = .88) and test-retest reliability (r = .78) were high. The Urdu version of PANAS is a valid and reliable measure of self-esteem for Urdu-speaking populations in Pakistan.